Loss of CTRP4 alters adiposity and food intake behaviors in obese mice - Sarver, Dylan C. (Am J Physiol Endocrinol Metab, 2020)
Central and peripheral mechanisms are both required for proper control of energy homeostasis. Among circulating plasma proteins, C1q/TNF-related proteins (CTRPs) have recently emerged as important regulators of sugar and fat metabolism. CTRP4, expressed in brain and adipose tissue, is unique among the family members in having two tandem globular C1q domains. We previously showed that central administration of recombinant CTRP4 suppresses food intake, suggesting a central nervous system role in regulating ingestive physiology. Whether this effect is pharmacological or physiological remains unclear. We used a loss-of-function knockout (KO) mouse model to clarify the physiological role of CTRP4. Under basal conditions, CTRP4 deficiency increased serum cholesterol levels and impaired glucose tolerance in male but not female mice fed a control low-fat diet. When challenged with a high-fat diet, male and female KO mice responded differently to weight gain and had different food intake patterns. On an obesogenic diet, male KO mice had similar weight gain as wild-type littermates. When fed ad libitum, KO male mice had greater meal number, shorter intermeal interval, and reduced satiety ratio. Female KO mice, in contrast, had lower body weight and adiposity. In the refeeding period following food deprivation, female KO mice had significantly higher food intake due to longer meal duration and reduced satiety ratio. Collectively, our data provide genetic evidence for a sex-dependent physiological role of CTRP4 in modulating food intake patterns and systemic energy metabolism.